ASSESSING THE POTENTIAL OF DULAGLUTIDE IN DE-INTENSIFICATION OF BACKGROUND ORAL GLUCOSELOWERING DRUG (OGLD) AND INSULIN THERAPY IN MALAYSIANS WITH TYPE 2 DIABETES MELLITUS - Hussein, Zanariah; Hui, Foo Siew; Nee, Low Yen; Adam, Noor Lita (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Many Malaysian T2DM patients are on multiple glucoselowering drugs (i.e. ≥2 OGLDs ± insulin). Dulaglutide, a once-weekly GLP-1RA, has been shown to significantly lower HbA1c levels in T2DM patients. However, there is a lack of real-world data to show the reduction of background treatment after patients start dulaglutide. METHODOLOGY This study aims to assess the potential of dulaglutide in deintensifying background OGLDs and total daily dose (TDD) of insulin in T2DM patients in a real-world clinical setting. This is a retrospective study of 45 T2DM patients who initiated dulaglutide in 3 Ministry of Health (MOH) hospitalbased endocrinologist-led diabetes clinics conducted in Hospital Putrajaya, Hospital Selayang and Hospital Tuanku Ja’afar. The primary outcome was a change in OGLDs and insulin therapy at 6 and 12 months of dulaglutide therapy. RESULTS At baseline, 91% (n = 41) of patients were on ≥2 OGLDs, while 82% (n = 37) were on insulin therapy with a mean baseline TDD of 64 units. After 6 months of dulaglutide therapy, 18% (n = 8) of the patients had at least one of their OGLD doses reduced, 38% (n = 17) of patients were able to stop one OGLD, and 4% (n = 2) of patients were even able to stop two OGLDs. At 12 months, 22% (n = 10) of patients had at least one of their OGLD doses reduced, 40% (n = 18) of patients were able to stop one OGLD, 9% (n = 4) of patients were able to stop two OGLDs from baseline, 56% (n = 25) of insulin-treated patients on dulaglutide had a TDD reduction of 23 units (-36%) at 6 months and 19 units (-30%) at 12 months. CONCLUSION Dulaglutide, with its once-weekly dosing, can effectively simplify patients' diabetes treatment by allowing the reduction of OGLDs and TDD of insulin. This de-intensification of medication could reduce the medication burden on patients and lessen the total drug cost for T2DM patients.